2015
DOI: 10.1016/j.ins.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A survey on fingerprint minutiae-based local matching for verification and identification: Taxonomy and experimental evaluation

Abstract: Fingerprint recognition has found a reliable application for verification or identification of people in biometrics. Globally, fingerprints can be viewed as valuable traits due to several perceptions observed by the experts; such as the distinctiveness and the permanence on humans and the performance in real applications. Among the main stages of fingerprint recognition, the automated matching phase has received much attention from the early years up to nowadays. This paper is devoted to review and categorize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 168 publications
0
71
0
Order By: Relevance
“…Daniel Peralta et al, 2015 [9] Fingerprint recognition had found a reliable application for verification or identification of 32 people in biometrics. Worldwide, fingerprints can be viewed as respected traits due to several 33 perceptions observed by the experts; such as the distinctiveness and the permanence on 34 humans and the performance in real applications.…”
Section: Figure-1 Convolution Based Filtration Of Latent Fingerprintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daniel Peralta et al, 2015 [9] Fingerprint recognition had found a reliable application for verification or identification of 32 people in biometrics. Worldwide, fingerprints can be viewed as respected traits due to several 33 perceptions observed by the experts; such as the distinctiveness and the permanence on 34 humans and the performance in real applications.…”
Section: Figure-1 Convolution Based Filtration Of Latent Fingerprintsmentioning
confidence: 99%
“…using the frequency domain for estimation of local orientation and ridge distance. Buades et al proposed a decomposition of the signal of the fingerprint image into two components [9]. Local Total Variation is used as a measure for sensibility regarding smoothing operations.…”
Section: Figure-1 Convolution Based Filtration Of Latent Fingerprintsmentioning
confidence: 99%
“…Although there are several ways to perform a matching between two fingerprints, many matching algorithms use the minutiae [3,7,29], comparing two minutiae sets to return a similarity score. The matching is performed once for each comparison between two fingerprints.…”
Section: Preliminariesmentioning
confidence: 99%
“…When two fingerprints are to be compared, the minutiae are extracted from the images, and then a matching algorithm is applied over the two minutiae sets to determine a similarity level. There are multiple proposals of minutiae-based matching algorithms in the literature [7]. Some of them are very efficient due to their simplicity [8], while others are very accurate [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are different methods in literature that lets Minutiae matching based on types of features [29][30] [31] or on correlations of image [28].…”
Section: The Minutiae Matching Phasementioning
confidence: 99%